Determination of Frequency of Increased Carotid Intimal Media Thickness Among Patients With Non-Alcoholic Fatty Liver Disease - Zahra, Shan E; Kamal, Mahjabeen Mahmood; Awan, Muhammad Wasim; Ishtiaq, Bushra; Usmani, Naila Nasir; Zahra, Fatima Tuz (Biological and Clinical Sciences Research Journal, 2025)
Non-alcoholic fatty liver disease (NAFLD) has been linked to early atherosclerosis, for which carotid intima-media thickness (CIMT) is a validated surrogate. Determining how often CIMT is elevated in NAFLD and whether the severity of hepatic steatosis tracks with CIMT can guide cardiovascular risk stratification. Objective: The objective of this study is to determine the frequency of increased carotid intima-media thickness (CIMT) among patients with non-alcoholic fatty liver disease (NAFLD) and to assess the potential association between NAFLD severity, metabolic risk factors, and CIMT elevation. Methods: After ethical approval from the institutional review board, this cross-sectional study was conducted at the Department of Radiology, KRL Hospital, Islamabad, from 1st August 2024 to 31st January 2025, after obtaining informed written consent from patients. Using non-probability consecutive sampling, 100 patients aged 18-70 years diagnosed with NAFLD by ultrasonography. Patients with a prior history of some cardiovascular disease, stroke, diabetes, acute or chronic liver disease, and those on medication affecting lipid profile were excluded from the present study. Results: The study of 100 patients with non-alcoholic fatty liver disease (NAFLD) found a mean age of 48.7 ± 11.5 years, with 58% male and 42% female. The mean BMI was 26.7 ± 4.7 kg/m², and 56% of participants had increased carotid intima-media thickness (CIMT) (mean 1.04 ± 0.27 mm). No significant associations were found between increased CIMT and age, gender, BMI, or NAFLD severity (p > 0.05). Conclusion: Metabolic syndrome should possibly have a greater influence on subclinical atherosclerosis in patients with NAFLD. However, these relations deserve further investigation in upcoming in-depth studies.